Emergency Information Forms for Children With Medical Complexity: A Qualitative Study. Issue 6 (June 2020) - Copper, Tara Conway; Jeffe, Donna B.; Ahmad, Fahd A.; Abraham, George; Yu, Feliciano; Hickey, Brianna; Schnadower, David
Abstract : Objectives: Children with medical complexity (CMC) are at risk for poor outcomes during medical emergencies. Emergency information forms (EIFs) provide essential medical information for CMC during emergencies; however, they are not widely used. We sought to identify factors related to optimal care for CMC to inform development of EIFs for CMC. Methods: We interviewed 26 stakeholders, including parents of CMC, healthcare providers, health information technology, and privacy compliance experts. We inquired about barriers and facilitators to emergency care of CMC, as well as the desired content, structure, ownership, and maintenance of an EIF. Audio recordings were transcribed and analyzed inductively for common themes using thematic analysis techniques. Results: Providers identified problems with documentation and poor caregiver understanding as major barriers to care. Parents reported poor provider understanding of their child's condition as a barrier. All groups reported that summary documents facilitate quality care. Recommended content included demographic/contact information, medical history, medications, allergies, advance directives, information about the patient's disease, and an action plan for anticipated emergencies. Twenty-three participants indicated a preference for electronic EIFs; 19 preferred a Web-based EIF that syncs with the medical record, with paper or portable electronic copies. Although 13 participants thought that EIFs should be patient owned to ensure availability during emergencies, 19 expected medical providers to create and update EIFs. Conclusions: Stakeholders interviewed reported a preference for Web-based, sync-capable EIFs with portable copies. Emergency information forms could be maintained by providers but owned by patients to optimize emergency care and align with the concept of the medical home.